Indonesian EFL secondary school students’ self-regulated writing strategies - Salsabila, Shalfa; Hapsari, Astri (JEES (Journal of English Educators Society), 2026)
Although EFL writing is considered a challenging skill for secondary school students to learn, there are still a few studies discussing how Indonesian EFL students use self-regulated writing strategies in their writing lessons. This survey study aims to discuss self-regulated writing strategies used by Indonesian secondary school students and identify whether gender differences exist in students’ use of self-regulated writing strategies. Sixty-five grade 12 students from a high school in Yogyakarta, Indonesia, agreed to participate in the study. The findings reveal that the profile of the participants’ writing self-regulated learning strategies, from the most frequently employed to the least frequently employed are: metacognitive judgment  (M = 5.59, SD = 1.26), goal-oriented monitoring (M=5.23, SD=1.27), memorization (M=5.14, SD=1.27), emotional control (M=5.13, SD=1.29), writing planning (M=5.11, SD=1.32), and goal-oriented evaluation (M = 5.10, SD = 1.22). It also revealed that female students tended to employ more self-regulated writing strategies than their male counterparts. This study suggests that the teacher should optimize students’ use of writing self-regulated learning strategies by raising students awareness of the strategies in the classroom instruction. For future study, a correlation study between writing self-regulated learning strategies and students’ writing performance will enrich the discussion on how writing strategies may give benefits to students’ writing performance.